Effects of replacing dietary fat with lecithin on broiler chicken zootechnical performance - Azman, MA; Ciftci, M (Ecole Nationale Veterinaire Toulouse, 2004)
The aim of this study was to investigate the effects of soybean lecithin (SL) as substitute for Soybean Oil (SO) or Beef Tallow (BT) added in broiler diets on growth. Four hundred 5-day-old chicks were divided into 4 equal groups receiving eventually SL-supplemented starter diets for 17 days and grower diets for 14 days. SO was gradually replaced by SL in diets with a rate of 0% (control group, n = 100), 25% (SL1 group, n = 100), 50% (SL2 group, n = 100). An another group (TL group, n = 100) received a dietary fat mixture containing 50% BT and 50% SL. Although birds presented comparable body weights at the end of experiment, a slight increase of daily weight gain was observed in SLI group during the growing period while this parameter was reduced in TL group in the same period. Even if decreases of food intake were noticed during starter and grower periods and for all the treatment duration in SL2 group, no significant improvement of food conversion ratio was obtained. On the contrary, during growing period and during all the treatment period, food intake was significantly enhanced in TL group, leading to significant increases of food conversion ratio. In conclusion, the substitution for SO by lecithin in dietary fat did not notably improve fat assimilation in gastrointestinal tract of young birds and did not lead to enhancement of broiler zootechnical performances.
Keywords: lecithin; broiler; fat; growth